2013
DOI: 10.1021/ie3030642
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Equilibrium and Process Design of CuSO4 + NaCl + (H2O or H2SO4/H2O) Systems at 298.15 K

Abstract: The low availability of fresh water in Chilean deserts has encouraged research into new alternative water sources in the mining industry. One of alternative is the use of saline water; however, there are few data about this new approach. For the production of copper sulfate pentahydrated (CuSO 4 ·5H 2 O) crystals, the effect of NaCl in the crystallization area must be known; therefore, the solid−liquid equilibrium of the CuSO 4 + NaCl + (H 2 O or H 2 SO 4 /H 2 O) system at 298.15 K was experimentally determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Fig. 8 shows the previously published phase equilibrium diagram for the system CuSO 4 + NaCl + (0.1 g H 2 SO 4 /g H 2 O) at 298.15 K [16]. In this previous work, Rocha et al found that adding NaCl has a clear effect on the solid-liquid equilibrium, promoting the formation of solid Table 5).…”
Section: Phase Diagrams and Propertiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Fig. 8 shows the previously published phase equilibrium diagram for the system CuSO 4 + NaCl + (0.1 g H 2 SO 4 /g H 2 O) at 298.15 K [16]. In this previous work, Rocha et al found that adding NaCl has a clear effect on the solid-liquid equilibrium, promoting the formation of solid Table 5).…”
Section: Phase Diagrams and Propertiesmentioning
confidence: 85%
“…However, the study did not involve the size and shape of the product, which could be affected by the addition of ethanol. Rocha et al [16] studied the solid-liquid equilibrium of the CuSO 4 + NaCl + (H 2 O or H 2 SO 4 /H 2 O) system at 298.15 K by the wet residue method. The density and refractive index of saturated solutions were also measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mining industries are developing new methods to optimize water use (Torres et al, 2013). In northern Chile, for example, certain mining companies are using raw seawater in their production processes (Rocha et al, 2013) and purified seawater by reverse osmosis (Philippe et al, 2010). In a mining process, the solid−liquid equilibrium and physical properties of solutions change upon seawater incorporation, especially the density and viscosity; which are used in pipe-sizing and pumping calculations.…”
Section: Introductionmentioning
confidence: 99%